A New Perspective on the Antimicrobial Mechanism of Berberine Hydrochloride Against Staphylococcus aureus Revealed by Untargeted Metabolomic Studies - Wu, Shu; Yang, Kun; Hong, Yuhang; Gong, Yanju; Ni, Jiajia; Yang, Ni; Ding, Weijun (Frontiers in Microbiology, 2022)
Berberine hydrochloride (BBR) is a natural product widely used in clinical medicine and animal production. It has broad-spectrum antibacterial activity, but its complex antibacterial mechanism has not been clarified. This study aimed to discover the metabolic markers and gain a new perspective on the antibacterial mechanism of BBR. The effects of different inhibitory concentrations of BBR on the survival and growth of standard strain Staphylococcus aureus ATCC 25923 were analyzed by bacteriostatic activity test. Differences in intracellular metabolites of S. aureus following 19 μg/mL BBR-exposure for 1-hour were investigated by combining non-targeted metabolomics techniques of gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS). The results showed that the minimum inhibitory concentration of BBR against S. aureus was 51 μg/mL. Total of 368 and 3454 putative metabolites were identified by GC-MS and LC-MS analyses, respectively. Principal component analysis showed separation of intracellular metabolite profiles between BBR-exposed samples and non-exposed controls. Pathway activity profiling analysis indicated a global inhibition of metabolisms by BBR-exposure, while enhancement was also found in nucleic acid metabolism, amino sugar and nucleotide sugar metabolism. Several metabolic markers were screened out mainly based on their variable importance of projection values. Two pyridine dicarboxylic acids were significantly down regulated, suggesting the reduction of stress resistance. The oxidized phospholipid (PHOOA-PE) was accumulated, while lipid antioxidant gamma-tocopherol was decreased, and farnesyl PP, the synthetic precursor of another antioxidant (staphyloxanthin), was decreased below the detection threshold. These evidences indicate that BBR reduced the antioxidant capacity of S. aureus. Accumulation of the precursors (UDP-GlcNAc, CDP-ribitol, and CDP-glycerol) and down-regulation of the key metabolite D-Ala-D-Ala, suggesting the inhibition of cell wall synthesis, especially the peptidoglycan synthesis. Metabolites involved in shikimate pathway (such as 3-dehydroshikimate) and downstream aromatic amino acid synthesis were disturbed. This study provides the first metabolomics information on the antibacterial mechanism of BBR against S. aureus. The key metabolic markers screened in this study suggest that shikimate pathway, staphyloxanthin synthesis and peptidoglycan biosynthesis are new directions for further study of BBR antibacterial mechanism in the future.